(untitled) (KONFERENSIYA, 2025)
This article studies the role and importance of narrative voice and focalization as stylistic devices in J. Orwell’s 1984. The research focuses on how the narrator’s voice and the point of view of the characters affect the reader’s understanding of the story and how they show the totalitarian society. The article also explains the different types of focalization and how they are used to describe characters. For example, the third person limited voice allows the reader to see Winston Smith’s thoughts, fears, and inner struggles closely. This helps the reader understand the control and psychological pressure in a totalitarian society. The analysis shows that narrative voice and focalization together are important tools to explain the main themes of the novel, such as oppression, control, the desire for freedom, and inner resistance. These stylistic devices help Orwell show the characters’ feelings clearly and emotionally, making the events more dramatic and impressive for the reader.